The changing relationship between civic engagement and paid work of women in a rural area in the Netherlands, 1993-2007 - Fortuijn, Joos Droogleever; Thissen, Frans (Hagar: Studies in Society and Culture, 2013)
In "Bowling alone: America’s declining social capital," Robert Putnam (1995) discusses the decline in civic engagement in the United States. According to Putnam, the increasing labor market participation of women is one of the main factors that explain the decline in civic engagement. This factor refers to the time availability hypothesis in social capital theory. A contrasting theory, the integration hypothesis, presupposes a positive correlation between participation in paid work and civic engagement. This article analyzes the changes in civic engagement and paid work of women in a rural area in the northern part of the Netherlands. Analysis is based on a survey and semi-structured interviews with women aged 18-50 in 1993 and in 2007. Over tliis period, the labor market participation of women increased substantially, while civic engagement decreased. Part of the decline in civic activity could be explained by the increasing participation in paid work, which is in accordance with Putnam’s time availability hypothesis. However, in 2007, civic engagement appeared to go hand in hand with participation in paid work, which is in line with the integration hypothesis.